The proximity of a highway increases CO2 respiration in forest soil and decreases the stability of soil organic matter - Dawid Kupka (Nature Portfolio, 2021)
Abstract Roadways traverse many forest areas and they often have harmful effects on forest soils, including the modified stability of soil organic matter (SOM). Soil CO2 respiration is an important indicator of SOM biological stability. The aim of this study was to test the hypotheses that a roadway will (1) modify the composition of the cation exchange capacity of adjacent forest soils, and (2) significantly decrease the stability of SOM. Two study sites were established in Scots pine and Silver fir stands, located close to the S7 highway in central Poland, which was opened to traffic in 1984. From each site, samples were taken at 2, 12 and 22 m from the forest edge. Soil CO2 respiration was determined using closed chamber incubation with an alkali trap. We also conducted a comprehensive analysis of soil chemical properties. The stoichiometric ratios of chosen chemical parameters to total carbon (Ct) were calculated. In both sites, we observed increased soil pH and CO2 respiration in the vicinity of the highway, as well as increased ratios of exchangeable calcium (Ca), magnesium (Mg) and sodium (Na) to Ct. In the fir site, the humic and fulvic acids, the dissolved organic carbon (DOC) content and aluminum (Al) to Ct ratio were depleted in close proximity to the highway. We suggest that the combined effect of Ca and Na ions, originating from winter de-icing, caused the depletion of Al and hydrogen (H) in the soil close to the forest edge and, therefore, resulted in lower SOM stability expressed as the decreased DOC and pyrophosphate-extractable carbon content, as well as the release of CO2. We conclude that the changes of SOM stability with distance were the effect of modification of ion-exchange relationships (particularly base cations versus Al3+ with H+) rather than forest stand species or intrinsic SOM properties (like functional groups, the recalcitrance of bindings etc.). Our work supports earlier studies, confirming the significant impact of Al and H on SOM stability.